Association between uncooperativeness and the glucose metabolism of patients with chronic behavioral disorders after severe traumatic brain injury: a cross-sectional retrospective study - Tomohiro Yamaki; Kosuke Suzuki; Yusuke Sudo; Tomihisa Niitsu; Masahiko Okai; Nobuo Oka; Masaru Odaki (BioPsychoSocial Medicine, 2018)
Abstract Bakground Patients with behavioral disorders following severe traumatic brain injury (sTBI) often have disorders of consciousness that make expressing their emotional distress difficult. However, no standard method for assessing the unsettled and unforeseen responses that are associated with behavioral disorders has yet to be established. Because the thalamus is known to play a role in maintaining consciousness and cognition, we used 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG-PET/CT) to examine the association between brain glucose metabolism in the thalamus and behavioral disorders. Methods We retrospectively analyzed 70 consecutive patients with sTBI who had been involved in motor vehicle accidents. To assess behavioral disorders, we evaluated 18 symptoms using the Brief Psychiatric Rating Scale (BPRS): Emotional Withdrawal, Conceptual Disorganization, Tension, Mannerisms and Posturing, Motor Retardation, Uncooperativeness, Blunted Affect, Excitement, Somatic Concern, Anxiety, Feeling of Guilt, Grandiosity, Depressive Mood, Hostility, Suspiciousness, Hallucinatory Behavior, Unusual Thought Content, and Disorientation. First, we identified clinical characteristics of sTBI patients with behavioral disorders. Next, we retrospectively analyzed 18F-FDG-PET/CT data to assess how thalamic activity was related with abnormal behaviors. Results Twenty-six patients possessed the minimum communicatory ability required for psychiatric interview. Among them, 15 patients (57.7%) were diagnosed with behavioral disorder, 14 of whom had reached a stable psychiatric state after about 426.6 days of treatment. Excitement (13 patients) and uncooperativeness (10 patients) were the most frequently observed symptoms. Available 18F-FDG-PET/CT data indicated that thalamic glucose metabolism was imbalanced and lateralized (p = 0.04) in 6 patients who exhibited uncooperativeness. Conclusions Behavioral symptoms of excitement and uncooperativeness were common in patients with sTBI, although most symptoms improved as the chronic stage continued. Our data support the idea that imbalanced laterality of glucose metabolism in the thalamus might be related to behavioral disorders characterized by uncooperativeness. Trial registration UMIN 000029531. Registered 27 March 2017, retrospectively registered.